2021
DOI: 10.1016/j.chest.2021.07.2016
|View full text |Cite
|
Sign up to set email alerts
|

Reveal Lite 2 Risk Assessment in Patients With Pulmonary Arterial Hypertension From the Griphon Study: A Post-Hoc Analysis Demonstrates Association of Risk Status With Long-Term Outcomes

Abstract: Risk assessment is key for optimal management of patients (pts) with pulmonary arterial hypertension (PAH). REVEAL Lite 2 (RL2) is a non-invasive risk assessment tool for PAH. In this post-hoc analysis of the GRIPHON study (NCT01106014), RL2 was applied to assess its prognostic and predictive value in PAH pts randomized to selexipag, a selective IP prostacyclin receptor agonist, or placebo.METHODS: RL2 was used to calculate risk score and pts were categorized into low, intermediate and high-risk strata at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies that applied risk scores to clinical trials as post hoc analyses or exploratory endpoints have previously suggested that risk scores distinguish between treatment arms in clinical trials 15,18,20–22 ; however, an individual patient data meta‐analysis of the SERAPHIN, GRIPHON, and AMBITON clinical trials did not find that risk scores were predictive of long‐term outcomes 23 . REVEAL 2.0 and REVEAL Lite 2.0 have been shown to predict prognosis in individual patients on treatment and have excellent concordance indices (> 0.7), 24–27 demonstrating that they may have the potential to be used in clinical practice. Risk scores can be seen as more clinically meaningful than single endpoints, with a dynamic relationship between changes in score and changes in outcome, a key requirement for surrogate endpoints 28 ; however, further refinement of risk scores may be necessary to infer surrogacy.…”
Section: Composite Endpointsmentioning
confidence: 99%
“…Studies that applied risk scores to clinical trials as post hoc analyses or exploratory endpoints have previously suggested that risk scores distinguish between treatment arms in clinical trials 15,18,20–22 ; however, an individual patient data meta‐analysis of the SERAPHIN, GRIPHON, and AMBITON clinical trials did not find that risk scores were predictive of long‐term outcomes 23 . REVEAL 2.0 and REVEAL Lite 2.0 have been shown to predict prognosis in individual patients on treatment and have excellent concordance indices (> 0.7), 24–27 demonstrating that they may have the potential to be used in clinical practice. Risk scores can be seen as more clinically meaningful than single endpoints, with a dynamic relationship between changes in score and changes in outcome, a key requirement for surrogate endpoints 28 ; however, further refinement of risk scores may be necessary to infer surrogacy.…”
Section: Composite Endpointsmentioning
confidence: 99%